2020
DOI: 10.1155/2020/3954084
|View full text |Cite
|
Sign up to set email alerts
|

Joint Pricing and Inventory Management of Interbasin Water Transfer Supply Chain

Abstract: Four game-theoretical decision models without/with backlogging for the interbasin water transfer (IBWT) supply chain considering water delivery loss under joint pricing and inventory management (JPIM) are first developed, analyzed, and compared; then, the corresponding numerical and sensitivity analyses are conducted and compared; finally, the managerial insights and practical implementations are summarized in this paper. The research results indicate that (1) a revenue and cost sharing contract could effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In 2019, water supply chain equilibrium and coordination were studied in [31]; in addition, fairness factors are considered to compare the supply chain performances, social welfare, and consumer surplus under different equilibrium strategies and coordination strategies. In 2020, literature [34] revealed that revenue and cost sharing contract could effectively coordinate and improve the water supply chain performance (Figure 1 and Table 1).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2019, water supply chain equilibrium and coordination were studied in [31]; in addition, fairness factors are considered to compare the supply chain performances, social welfare, and consumer surplus under different equilibrium strategies and coordination strategies. In 2020, literature [34] revealed that revenue and cost sharing contract could effectively coordinate and improve the water supply chain performance (Figure 1 and Table 1).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the literature of Chen and Wang [12], the operational strategy and policy for internal incentives and subsidy in a water-saving service supply chain under the scenario with maximum social welfare are discussed. Chen and Chen [13] developed, analyzed, and compared four decision models of game theory in two cases of considering or without considering backlogging for the interbasin water transfer supply chain. Loss of water transport in the condition of joint pricing and stock management is considered.…”
Section: Literature Reviewmentioning
confidence: 99%